Analysis of Marine Products Export from India using Markov-Chain Analysis - Chandrasekar, V.; Paramasivam, P.; Jayanthi, C.; Sathy, R.; Gopal, Nikita; Mani, K. (Fishery Technology, 2020)
The present study analyses the changing pattern of marine product exports from India to seven regions/ countries such as Japan, USA, European Union (E.U), China, South East Asia (SEA), Middle East (ME) and others, during two decades from 1995 to 2015. The average growth rate of marine seafood export in relation to quantity and value for the two decades was 6.78 and 12.5% respectively. Frozen shrimp export quantity had nearly 40% share in the total export basket. Instability in value was higher than the quantity of export, out of which frozen shrimp price instability was nearly 60%. Using Markov Chain Analysis, it was observed that European Union was having higher probability of retention (0.82) compared to the other regions. In the first decade Japan was the major importer with higher probability of retention which reduced from 0.91 to 0.56 during the second decade with a gain by European Union (0.87) in the same decade. Â